Platelet activation in the presence of neutral protamine Hagedorn insulin: a new feature of antibodies against protamine/heparin complexes. (30th November 2016) - Zöllner, H.; Jouni, R.; Panzer, S.; Khadour, A.; Janzen, L.; Wesche, J.; ten Berg, M.; Schellong, S.; Heinken, A.; Greinacher, A.; Bakchoul, T.
Abstract : Essentials Protamine (PRT) is used to stabilize insulin in neutral protamine Hagedorn (NPH) insulin. The interaction between NPH‐insulin, anti‐PRT/heparin antibodies and platelets was investigated. Anti‐PRT/heparin antibodies activate platelets in presence of NPH‐insulin dependent on heparin. Cross‐reactivity seems to have no major effect on the clinical outcome of medical patients. Summary: Background: Protamine (PRT) is used to stabilize insulin in neutral protamine Hagedorn (NPH) insulin, a commonly used therapeutic agent for diabetes mellitus. Immunization against PRT/heparin complexes is common in diabetic patients. Objectives: To investigate the impact of NPH‐insulin on the interaction between anti‐PRT/heparin antibodies and platelets. Methods: The interaction between NPH‐insulin and anti‐PRT/heparin antibodies was tested using in‐house enzyme immunoassays. The ability of anti‐PRT/heparin antibodies to activate platelets in the presence of NPH‐insulin (and heparin) was investigated using flow cytometry. Results: Twenty‐one out of 80 sera containing anti‐PRT/heparin IgG showed binding to NPH‐insulin. Anti‐PRT/heparin IgG from immunized patients bound to platelets in the presence of NPH‐insulin, but not in the presence of native insulin. Anti‐PRT/heparin antibodies induced P‐selectin expression in the presence of NPH‐insulin in a heparin‐dependent way (median mean fluorescence intensity in the presence of NPH‐insulin: 55, 95% confidence interval [CI] 18.7–100.5 vs. NPH‐insulin and heparin: 204, 95% CI 106.5–372.8). The clinical relevance of platelet‐activating anti‐PRT/heparin antibodies was assessed by investigating a multicenter study cohort of 332 acutely ill medical patients who received heparin. None of the 21 patients with anti‐PRT/heparin IgG developed thrombocytopenia or thromboembolic complications. Conclusions: Anti‐PRT/heparin antibodies activate platelets in the presence of NPH‐insulin in a heparin‐dependent way. However, results from our preliminary study indicate no major impact of these antibodies on the clinical outcome in medical patients receiving heparin, particularly on thromboembolic complications.